2014
DOI: 10.14203/reinwardtia.v14i1.421
|View full text |Cite
|
Sign up to set email alerts
|

A Physiological Approach to Conservation of Four Palm Species: Arenga Australasica, Calamus Australis, Hydri- Astele Wendlandiana and Licuala Ramsayi

Abstract: Palms (Arecaceae) are an important component of many tropical rainforests. Many have also been cultivated widely for agricultural commodities with high economic value. They are also important components in rehabilitation of disturbed or marginal lands. Knowledge and application of germination strategies are essential in the cultivation of palms. Many species have seeds that do not germinate readily, even when light conditions are favourable. This research determined the effects of seed coats, light and tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…An allometric equation was developed for Pandanus atrocarpus providing an estimated total biomass and carbon of 5.16 ton/ha containing 2.42 ton C/ ha. The underground C with the mean peat depth of 5.5 m, mean bulk density of 0.18 g/cm 3 , and the mean organic C of 46.6 % was 464,895.94 ton C/ha. In the entire conservation forest area of 541 ha the total aboveground biomass and carbon storage was estimated to be 80,708.64 ton and 37,934.00 ton C, while the total underground carbon was 238.96 million MTC.…”
Section: The Structurementioning
confidence: 94%
“…An allometric equation was developed for Pandanus atrocarpus providing an estimated total biomass and carbon of 5.16 ton/ha containing 2.42 ton C/ ha. The underground C with the mean peat depth of 5.5 m, mean bulk density of 0.18 g/cm 3 , and the mean organic C of 46.6 % was 464,895.94 ton C/ha. In the entire conservation forest area of 541 ha the total aboveground biomass and carbon storage was estimated to be 80,708.64 ton and 37,934.00 ton C, while the total underground carbon was 238.96 million MTC.…”
Section: The Structurementioning
confidence: 94%
“…It is a type of germination in which the cotyledonary petiole elongates, radicle and plumule emerges from the cotyledonary sheath [47]. From the germination studies of A. australasica it is evident that the untreated seeds showed low germination rates when compared with scarified or heat-treated seeds [17]. Secondary dormancy is a phenomena observed in their seeds which refers to the ability of the seeds to remain dormant in unfavorable conditions, germinate and establish when conditions are favorable for its establishment [48][49][50][51].…”
Section: Seed Biology Of Arengasmentioning
confidence: 99%
“…Latifah et al, (2014) found that extract of A. pinnata can reduce pain and inflammation in rats Li et al, (2020). investigated anti-inflammatory activity determined by ELISA (enzyme-linked immunosorbent assay) and real-time PCR was used to study the expression level of tumor necrosis factorα (TNFα), interleukin-1β (IL-1β), cyclooxygenase-2 (COX-2), and prostaglandin E2 (PGE).…”
mentioning
confidence: 99%